Idiopathic ileal volvulus with multiple concomitant infections in a starving man - Tan, Lii Jye; Othman, Mohammad Shafie; Hiu, Jessie; Wong, Kum Thong; Lai, Shau Kong (Malaysian Society of Pathologists, 2021)
Background: Small bowel volvulus is defined as the torsion of the small intestine, potentially leading to bowel obstruction, gangrene and perforation. It is a rare condition, especially in adults. Case presentation: A 30-year-old man was retrieved from the jungle with severe weight loss and abdominal symptoms. He succumbed to death despite 22 days of intensive medical treatment. An autopsy revealed a ruptured gangrenous ileal volvulus with peritonitis and subdiaphragmatic abscess. Further laboratory analysis detected systemic Candida tropicalis and intestinal gramnegative bacterial sepsis, systemic Zika virus viremia, leptospirosis complicating rhabdomyolysis and disseminated intravascular coagulopathy, Type I Herpes Simplex virus infection of the tongue and upper gastrointestinal tract. The cause of death was the ruptured ileal volvulus, complicated with upper gastrointestinal bleeding due to Herpes simplex virus esophagitis in a malnourished patient with resolving leptospirosis and underlying Zika virus co-infection. Conclusion: Rare clinical scenarios of adult-onset intestinal volvulus with concomitant multiple infections precludes clinical diagnosis and early treatment, leading to devastating consequences of clinical outcome. The positive clinical and postmortem correlation is a good learning lesson in many disciplines of medicine and science.